A luta das Abuelas de Plaza de Mayo e a solidariedade do clamor na restituição dos netos desaparecidos - Salles, Gabriela Sacche (2020)
This research has as its central object the struggle of the Abuelas of Plaza de Mayo to restore their grandchildren, children who disappeared during the Argentine dictatorship, as well as the representation that was attributed to them. Its analysis will be carried out through, on the one hand, its own publications and reports as a social movement and, on the other, through the contribution of the bulletins of the Defense Committee for Human Rights for the Southern Cone Countries - CLAMOR, specifically on the publications created around the issue of the disappearance of children and the abductions of pregnant women in the Latin American context. As a problem we explored how this historical process reflected on the construction of the memory left by the Grandmothers' performance. Thus, we aim to understand the discursive construction that Abuelas weave around their struggle, their search strategies for missing grandchildren, as well as to define the role played by the CLAMOR group in favor of the Abuelas' cause